Antioxidative and anti-inflammatory activities of Hibiscus cannabinus L. leaf aqueous extract and its potential benefit in experimental atherosclerosis in vitro - Arapoc, Daryl Jesus (2014)
Kenaf or scientifically known as Hibiscus cannabinus has been reported to be widely cultivated in West Africa, Bangladesh, India and Southern China. The objective of this study is to evaluate the nutritional composition of H. cannabinus leaf as well as its in vitro antioxidant activities and anti-inflammatory properties towards human umbilical vein endothelial cell (HUVEC). Fresh H. cannabinus leaves were collected from Taman Pertanian Universiti, Universiti Putra Malaysia (UPM). The mixture of the dried powder leaf and water were incubated in the water bath at 40°C for 12 hour in order to produce the aqueous extract. Proximate, elemental and vitamins analysis were done on fresh H. cannabinus leaves to determine the nutritional composition. Then, 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay and Ferric Reducing/Antioxidant Power (FRAP) assay was done on H. cannabinus leaves aqueous extract to determine antioxidant power whereas the phenolic and flavonoid content of H. cannabinus leaves aqueous extract were assessed by total phenolic content (TPC) and total flavonoid content (TFC) assays. Cytotoxic assessment of H. cannabinus leaves aqueous extract was performed by exposing the HUVECs to the extract at concentrations ranging from 50 to 1000 μg/ml for 24 hr with complete medium. The inhibitory concentration (IC50) of hydrogen peroxide (H2O2) and the effective concentration (EC50) of H. cannabinus leaves aqueous extract in preventing H2O2–induced cell injury were assessed using the MTT assay. The antioxidative and anti-inflammatory effects of H. cannabinus leaves aqueous extract on H2O2–induced cell injury were carried out by seeding and divided HUVECs into three groups; the positive control (PC) group, HUVECs were exposed to either 250 μM H2O2 or 10 ng/ml TNF-α alone; the treated groups HUVECs were incubated with various concentrations of extracts (50, 100, 200 and 400 μg/ml) for 30 minutes prior exposured to H2O2 (250 μM) or TNF-α (10 ng/ml); the negative control (NC) groups, HUVECs were incubated with culture medium only. The cells were incubated for 24 hours at 37 oC with 5% CO2 supply for analysis of antioxidant enzymes activities (SOD, GPx and Catalase) and lipid peroxidation level (MDA) as well as anti-inflammatory effects (NO, VCAM-1, ICAM-1, MCP-1 and M-CSF). All results of this study were then statistically validated using one-way ANOVA, SPSS version 16. The result showed that H. cannabinus leaf contained carbohydrate, protein and fat with very high level of moisture with 79.2%. On the other hand, the leaf contained considerable values of Vitamin A, Vitamin C, Vitamin B1, Vitamin B2 and Vitamin E. For the mineral analysis, it was found that H. cannabinus leaf contained high level of potassium and calcium and other mineral traces were included magnesium, ferum, selenium, and zinc. The leaf phenolic content was 3.21 ± 0.10mg (GAE)/0.1gml-1 extract and the flavonoid content was 2.17±0.54 mg (QE)/0.1gml-1 extract. TPC and TFC results correlated positively with DPPH and FRAP with 92.4% and 3.8 μmol Fe (II) sulphate/g respectively. H. cannabinus leaves aqueous extract was found to be non-toxic to the cells as no inhibitory concentration (IC50) and significantly attenuate the cytotoxicity effect of H2O2 at 50μg/ml. H. cannabinus leaves aqueous extract doses within concentration range of 50-400 μg/ml protected the cells against cellular damage and caused significant reduction in the anti-oxidative enzyme (SOD, GPx and Catalase) activities (p<0.05/p<0.01) with reduction of NO production in comparison with the PC. Besides that, the expressions of VCAM-1, ICAM-1, MCP-1 and M-CSF in the H. cannabinus leaves aqueous extract-treated groups were lowered (p<0.05/p<0.01) than PC. These findings suggest that H. cannabinus leaf possesses antioxidative (polyphenols and flavonoid) and anti-inflammatory properties and that it attenuates the initial stage of atherogenesis in vitro.